An exploration of the surgical skill training curriculum for cardiac surgery residents. Issue 6 (18th April 2019) - Luo, Fuliang; Luo, Xiaokang; Li, Bo; Tang, Yue; Sun, Hansong
Abstract: Background: A "boot camp" program is commonly adopted in surgical skills training. Due to a shortage of cardiac surgeons, establishment of a well‐designed training curriculum for cardiac surgery residents is needed in developing countries. Methods: We established a comprehensive 3‐module training curriculum, including: (1) the cardiopulmonary bypass establishment technique, (2) coronary artery anastomosis and (3) basic surgical skills of thoracoscopy. Each module was designed for one technique, with a training time of 1 week. Each module included theoretical knowledge learning, demonstration by senior surgeons, and practice through simulators and in vivo animal experiment. A series of questionnaires were used to assess the training effect. Results: We organized 50 person‐times of training. The overall satisfaction of residents participating in the entire 3‐module training was 7.88 points (from a full score of 10 points). The satisfaction of each module was 8.94, 8.13, and 7.63, respectively. The survey suggested the training could increase trainees' confidence in the operation ( P  < 0.05). Some trainees also proposed some suggestions for the further improvement of the curriculum. Conclusions: It is feasible to develop a multimodule comprehensive surgical skill training curriculum for cardiac surgery residents in China, whose confidence can be effectively enhanced.